Radial variation of some anatomical features in Eusideroxylon zwageri and Potoxylon melagangai - Jusoh, Ismail; I. B, Ipor (Malaysian Science And Technology Congress 2002, 2002)
An anatomical study was done on two species ofwoods, namely Belian (Eusideroxylon zwageri) dan Malagangai (Potoxylon melagangai). The objectives were to determine differences between selected anatomical characteristics of both species and their trend in relation to radial direction. Measurement were done on macerated fibers and safraninstained sections of both species. Among the properties measured were fiber length, fiber wall thickness, vessel diameter, count per square millimeter and ray height. The data were analysed using one-way ANOV A and regression analysis. One-way ANOVA showed that the fiber length and fiber wall thickness ofE. zwageri was longer and thicker than that ofP. melagangai. Fibre length of Eusideroxylon zwageri increased while ray height decreased with radial direction. Positive trend ofincreased in size with radial direction of fiber length, fiber wall thickness and vessel diameter ofP. mela~angai was observed. No significant radial trend was observed for number of vessellmm and ray height in P. melagangai. This study showed that radial trend and anatomical characteristics of both species were not similar.